(untitled) (Journal of Enam Medical College, 2014)
Background: Upper gastrointestinal (GI) symptoms are common complaints affecting 25–40% of the general population and are common causes of health care utilisation and substantially affect the quality of life. In day-to-day practice our clinicians have to face good number of patients with various upper GI symptoms. But we have limited data on the prevalence of different upper GI symptoms in our community. Objective: The present study aimed to find out the prevalence of different upper GI symptoms in the general population of a district in Bangladesh. Materials and Methods: This population-based observational study was conducted in a selected district of Bangladesh. Three thousand subjects selected by cluster sampling method were interviewed by a valid bowel disease questionnaire. Students t test and chi-square tests were used for comparison of different variables with significance level set at 0.05. Results: Among the study population 1523 were men and 1477 were women with a mean age of 33.91 ± 16.43 years. A total of 2273 (75.8%) persons had at least one upper GI symptom, 2072 (69.1%) had 2 or more symptoms and 1705 (56.8%) had 3 or more symptoms in the prior 3 months. Nine hundred sixty three subjects (32.1%) had upper abdominal pain, 1265 (42.16%) had bloating, 1354 (45.13%) had heart-burn, 1166 (38.87%) had chest pain, 1347 (44.9%) had early satiation and 258 (8.6%) had vomiting. Around 249 (8.3%, male 123, female 126, P=0.691) was diagnosed as functional dyspepsia, 187 (6.2%, male 82, female 105, P=0.059) as gastroesophageal reflux disease (GERD) and 55 (1.83%, male 27, female 28, P=0.892) as upper abdominal bloating. Only one woman fulfilled the criteria for functional gallbladder or sphincter of Oddi dysfunction. Approximately 40.56% dyspeptic patients had overlapping GERD symptoms. Symptom prevalence was found to decrease with increased number, frequency and duration of symptoms. Conclusion: Upper GI symptoms are prevalent in our community. Multiple upper GI symptoms do exist simultaneously. Symptom prevalence varies with number, frequency and duration of symptoms. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19458 J Enam Med Col 2014; 4(2): 79–88